Review of Hierarchical set up of Central Forensic Science Laboratories - Singh, Dr Tajendra (Innovative Research Thoughts, 2018)
In forensic genetics, the interpretation of the findings of forensic genetic studies based on activity level proposals is a new field. Even though it has a lengthy history, it has never been deemed as crucial to the profession as it is now. When it comes to providing expert testimony, forensic biologists are increasingly needed to offer their specialized expertise to assist their clients understand how and when evidence was transferred and how it was maintained in court. This means that scientists have an important role in evaluating their results in the context of the situation. An activity-level inference can be made by the judiciary using proper case assessment and interpretation respecting the hierarchy of propositions (supported by the use of Bayesian networks as graphical models), as well as appropriate data to inform probabilities and international reporting guidelines. As shown by this critical evaluation of current research, evidence interpretation is possible when propositions of interest are at the 'action level' with appropriate training and quality assurance conditions.